ChemInform Abstract: Palladium/Copper‐Catalyzed Oxidative C—H Alkenylation/N‐Dealkylative Carbonylation of Tertiary Anilines. Issue 10 (11th March 2014) - Shi, Reny; Lu, Lijun; Zhang, Hua; Chen, Borui; Sha, Yuchen; Liu, Chao; Lei, Aiwen
Abstract For the first time the aerobic title reaction is presented and furnishes the products in moderate to good yields tolerating a variety of functional groups.